Preterm Birth - Erez, Offer (IntechOpen, 2013)
The preterm parturition syndrome is one of the major obstetrical complications of our time. Understanding the mechanisms leading to prematurity may assist the clinician to tailor the desired treatment that is suitable to the mechanisms leading to preterm birth in a specific patient. In the first section of this book we present an update on the association of periodontal disease, maternal stress, and activation of the hemostatic system and preterm parturition. The second section of the book deals with short and long term effects of prematurity, with a long term aspect of late preterm birth. This book will expand the dialogue between obstetricians, pediatricians and other disciplines regarding the diagnosis, treatment and prevention of prematurity.